Muhammad Iqbal's Creativity Concept And Its Implementation in Students' Psychological Understanding: Konsep Kreativitas Muhammad Iqbal Dan Implementasinya Dalam Pemahaman Psikologi Peserta Didik - Arham Junaidi Firman; Akhmat Noor Syofik; Anis Rahmawati (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
The world of education today began to be tarnished because of the frequent encounters of psychic or moral violence so that it is necessary to increase and develop the creativity of educators, especially in understanding the psychological condition of student. This study aims to examine critically and reflectively about the concept of creativity according to Muhammad Iqbal and its implementation in understanding the psychology of student. Data collection in this study was conducted through documentation techniques with secondary data sources as the primary data. Furthermore, data analysis is done through content analysis. The results of the study showed, namely First, the concept of creativity according to Muhammad Iqbal is part of the development of individuality that can be understood by exploring the conception of the nature and function of individuals through education. Second, the implementation of Muhammad Iqbal's concept of creativity in the psychological understanding of learners has a very urgent position in the world of education today.